2022
DOI: 10.1001/jama.2022.14663
|View full text |Cite
|
Sign up to set email alerts
|

Roflumilast for Chronic Plaque Psoriasis

Abstract: Plaque psoriasis is a multisystem inflammatory disease that affects children and adults. Skin lesions are the most prominent manifestation, appearing as localized or widespread red plaques with silvery scale. Psoriasis may be associated with arthritis, obesity, metabolic syndrome, psychiatric disease, impaired quality of life, and increased risk of cardiovascular disease. 1 The etiology and precise pathogenesis of psoriasis remain unclear. Treatment selection depends on body surface area affected, lesion chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Some case reports suggested that oral roflumilast may also be beneficial in psoriasis as an alternative systemic treatment, including in comorbidities such as metabolic syndrome or COPD. [51][52][53] The results of a recent company-independent double-blind, placebo-controlled, multicenter, randomized trial (PSORRO) 54 on 46 patients randomized 1:1 to roflumilast or placebo found that over a period of 24 weeks, oral roflumilast proved effective and safe in the treatment of moderate-to-severe plaque psoriasis.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Some case reports suggested that oral roflumilast may also be beneficial in psoriasis as an alternative systemic treatment, including in comorbidities such as metabolic syndrome or COPD. [51][52][53] The results of a recent company-independent double-blind, placebo-controlled, multicenter, randomized trial (PSORRO) 54 on 46 patients randomized 1:1 to roflumilast or placebo found that over a period of 24 weeks, oral roflumilast proved effective and safe in the treatment of moderate-to-severe plaque psoriasis.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…It encompasses four types, each characterized by distinct pathological features and clinical presentations: chronic plaque, pustular, erythrodermic, and articular psoriasis ( 5 , 6 ). Among these, chronic plaque psoriasis (commonly referred to as psoriasis vulgaris) is the most prevalent, accounting for approximately 85-90% of all cases ( 7 9 ). Psoriasis has a complicated etiology that involves genetic, epigenetic, and environmental variables ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“… 6 Oral roflumilast was approved first-in-class for treatment of severe COPD more than a decade ago, and generic versions are available in the United States (US). A topical formulation of roflumilast has recently been approved by the US Food and Drug Administration (FDA) for treatment of plaque psoriasis, 7 but the effect of systemic treatment with roflumilast in patients with psoriasis has not been explored.…”
Section: Introductionmentioning
confidence: 99%